The Chacoan bat fauna identity: patterns of distributional congruence and conservation implications - Sandoval, María Leonor (2013)
The aim of this paper is to characterize the Chaco thorn-scrub savanna as a unit, biologically defined by means of its identification as a regional pattern of distributional congruence, through the evaluation of the utility of bat assemblages as biogeographical indicators of the Chaco at regional scale, and to then evaluate this characterization in terms of the conservation value of this habitat. We have considered the whole territory of Paraguay and Bolivia, and the northern of Argentina; that is the entire Chaco biogeographic province, and part of the surrounding biogeographic provinces. We conducted an exhaustive search and constructed a database consisting in 9509 geo-referenced records showing that the bat fauna of the Chaco is richer than previously reported. We used an optimality criterion to identify patterns of distributional congruence determined by the distribution of bats. We recovered several areas that correspond with the Chaco. The areas that are coincident with the Chaco were supported by eight species: Eptesicus brasiliensis, E. diminutus, Eumops dabbenei, Histiotus velatus, Promops centralis, P. nasutus, Pygoderma bilabiatum, and Tonatia bidens. These results show that bat assemblages are useful as characterizing of regional patterns of distributional congruence. These patterns provide first-step testable hypotheses of areas of endemism for future analyses of neighboring regions or analyses at more inclusive scales. Bat assemblages may be used to characterize the Chaco despite the fact that it was thought this habitat lacked an identity in relation to its bat fauna. The Chacoan nature as a biologically distinctive natural unit is clear now also in terms of regional patterns of distributional congruence of bat species, which provides further evidence for intensifying efforts to protect this endangered habitat.